2015
DOI: 10.1530/erc-15-0137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumor cell plasticity by the androgen receptor in prostate cancer

Abstract: Prostate cancer (PCa) has become the most common form of cancer in men in the developed world, and it ranks second in cancer-related deaths. Men that succumb to PCa have a disease that is resistant to hormonal therapies that suppress androgen receptor (AR) signaling, which plays a central role in tumor development and progression. Although AR continues to be a clinically relevant therapeutic target in PCa, selection pressures imposed by androgendeprivation therapies promote the emergence of heterogeneous cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 169 publications
1
33
0
Order By: Relevance
“…For example, multiple studies have shown that AR inhibition through ADT can promote EMT. Conversely, aberrant AR signaling has been indicated in driving EMT in CRPC (reviewed in [48]). Similarly to these studies that highlight the cell-context-dependent regulation of EMT by AR, a previous study reported that Snail overexpression induced neuroendocrine prostate cancer (NEPC) differentiation in prostate cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, multiple studies have shown that AR inhibition through ADT can promote EMT. Conversely, aberrant AR signaling has been indicated in driving EMT in CRPC (reviewed in [48]). Similarly to these studies that highlight the cell-context-dependent regulation of EMT by AR, a previous study reported that Snail overexpression induced neuroendocrine prostate cancer (NEPC) differentiation in prostate cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it overlaps with “anaplastic prostate carcinoma” or “AVPC,” which are characterized by extensive visceral metastases, short response duration to ADT, sensitivity to platinum‐containing chemotherapy and poor prognosis . t‐NEPC develops as a consequence of lineage plasticity, a phenomenon in which tumor cells acquire phenotypic characteristics of a cell lineage whose survival is no longer regulated by a certain drug target . The incidence of t‐NEPC has been rising rapidly as a result of the increasing use of potent AR pathway inhibitors, and it is now imperative to study the molecular characteristic of this aggressive subtype and identify specific molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 t-NEPC develops as a consequence of lineage plasticity, a phenomenon in which tumor cells acquire phenotypic characteristics of a cell lineage whose survival is no longer regulated by a certain drug target. 15 The incidence of t-NEPC has been rising rapidly as a result of the increasing use of potent AR pathway inhibitors, and it is now imperative to study the molecular characteristic of this aggressive subtype and identify specific molecular targets. Recent integrative genomic analysis and novel in vivo models of t-NEPC have identified several key molecular features of NEPC.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the maintenance of AR activity, survival benefits are achieved by re-targeting AR signaling with next-generation AR-directed therapeutics, though responses are generally measured in months rather than years(10,11). While resistance is again often accompanied by persistent AR activity, prolonged and effective AR suppression can induce epithelial-to-mesenchymal-transition (EMT) (1214), acquisition of stem-like cell characteristics(13,1517), and trans-differentiation into an AR-null neuroendocrine phenotype. There are also significant complications and quality of life issues that arise with long-term ADT(18,19).…”
Section: Introductionmentioning
confidence: 99%